SURGICAL GINGIVECTOMY AND SUPERNUMERARY TOOTH EXTRACTION ON PATIENT WITH FIXED ORTHODONTIC APPLIANCE: A CASE REPORT - Nydia, Fidela Matta; Listy Putri, Izaz Zayyan; Aji Setiya, Reza Purwa; Sukmawati, Ayuda Nur (Indonesian Journal of Dentistry, 2025)
Background: Gingival enlargement is the most common characteristic of various conditions, such as inflammation, medication effects, systemic conditions like pregnancy, leukemia, and can also be caused by orthodontic treatment. There is a positive correlation between the duration of orthodontic appliance use and the incidence of gingival enlargement since it facilitates biofilm accumulation and bacterial colonization, which triggers the inflammation.Case: A 24-year-old female patient came to RSGM UNIMUS with complaints of swollen gums in the posterior maxilla and anterior mandible, causing her teeth to appear shorter. She has experienced this issue for the past five years since using fixed orthodontic appliances. Intraoral examination revealed significant swelling in almost the entire gingival region of both the upper and lower jaws, along with a conical supernumerary tooth in the anterior region of the lower jaw. Physiological pigmentation was noted in the anterior gingiva of the mandible, which is showing a brownish color. Radiographs showedhorizontal bone loss at the alveolar crest in the lower jaw. Gingivectomy with scaling and root planning, extraction of the supernumerary tooth, and depigmentation were planned for this case.Outcome: Following a one-month post-operative evaluation, the treatment outcomes for the patient were promising with minimal pain reported. She noted that her confidence in her appearance has significantly improved.Conclusion: The use of fixed orthodontic appliances is correlated with gingival enlargement due to several factors. These appliances can lead to increased plaque accumulation and biofilm formation around the brackets and wires, which triggers inflammation. The mechanical irritation from the appliances can also exacerbate the condition, making it harder for patients to maintain her oral hygiene.